Application of Low Cost Microcontroller in Rapid Control Prototyping for Single Phase Back to Back Converter - Aizam Zulkifli, Shamsul; Chakraver, Suraj (International Journal of Engineering and Technology, 2018)
This project is carried out in order to develop a Rapid Control Prototyping (RCP) process using a PI control which can be employed in a low cost microcontroller device for online measurement. Therefore, the Raspberry PI has been chosen for beeing set as a real-time response and combined with a closed loop feedback control. Here, a back to back converter has been developed using the Matlab-Simulink in order to interface in real time processing system. At the end, all the results have shown the desired output which responses to the target referenced which has been observed in real-time using Matlab Graphical User Interface model. It indicates that, the selected low cost microcontroller can be used as a real time measurement for reducing the total cost of experimented setup, ensure safety of the system and increase the accuracy of the system